Building Resilience and Attachment in Vulnerable Adolescents: The Feasibility of a Virtually Delivered Group Intervention for Adolescents with Suicidal Ideation and Their Caregivers - Nicole Sheridan; Allison Kennedy; Clare Gray; Leigh Dunn; Jayme Stewart; Hannah Elliott; Kendra Carnrite; Ademola Adeponle; Paula Cloutier (Telemedicine Reports)
Background: The COVID-19 pandemic required many interventions to be conducted virtually. Building Resilience and Attachment in Vulnerable Adolescents (BRAVA) is a group intervention designed for adolescents and their caregivers to reduce adolescent suicidal ideation (SI). Objective: We aimed to adapt BRAVA for virtual delivery and evaluate its acceptability and feasibility. Methods: We conducted an 8-week pre–post trial between October and December 2020. Six adolescents and six primary caregivers were recruited from a pediatric hospital in Ontario, Canada. Families completed a virtual intake and exit assessment together and 6 weekly BRAVA group sessions separately. Satisfaction feedback was collected after each group session and during their exit, and clinical outcomes were collected at intake and exit. Weekly team meetings were conducted to gather clinician feedback. Results: The study uptake rate was 42.9% of eligible participants. There were no dropouts. Adolescent and caregiver attendance rates for group sessions were high (median = 6). Most youth (83.4%) and caregivers (66.7%) reported that the virtual process worked well. All caregivers (100%) agreed they would participate in a virtual group session again, compared with youth (50%). Providers approved of the virtual adaptation but identified potential improvements (e.g., manual content, safety procedures). Adolescent SI decreased significantly post-treatment (Mpre = 50.7, Mpost = 29.7, p = 0.002). Conclusions: Virtual delivery of BRAVA is acceptable and feasible and may help reduce SI in adolescents. Uptake, retention, and satisfaction were high for adolescents and caregivers. Feedback collected will improve BRAVA for future evaluations, including a randomized controlled trial.